Symbiotic relationship between selected probiotic bacteria in chemostat culture - Jusoh, Normah (2000)
The effect of culture combination on growth of three strains of probiotic (Streptococcus jaecalis T-110, Bacillus mesentericus TO-A and Bifidobacterium breve G48) was examined using chemostat culture. Results of bacterial viable counts revealed that mixed culture of two probiotic microorganisms had higher growth rate compared to single culture of probiotic. The improvement of bacterial growth can be partly attributed to the production of certain growth factors by one microorganism that was capable of stimulating the growth of another bacterium. The metabolites in sample broth were determined using High Performance Liquid Chromatography (HPLC). It can be postulated that succmlC acid, argmme, vitamin B₁ and B₂ synthesised by B. breve 048 were used by S. faecalis T -110 to improve its growth. Furthennore, B. mesentericus TO-A was found to utilise vitamin B6 and fonnic acid produced by the respective S. faecalis T -110 and B. breve TO-A. In return, B. breve 048 utilised vitamin BI2 produced by B. mesentericus TO-A. The effect of mixed culture of probiotic on growth of pathogenic Escherichia coli V517 was also investigated in chemostat culture. Results showed that mixed culture of probiotic exerted better inhibitory effect against E. coli V 517 compared to single culture of probiotic. HPLC analyses showed that mixed culture of probiotic produced higher yield of lactic and acetic acids that are fatal to E. coli V 517. Meanwhile, ammonia was found not to be an important inhibitory agent to E. coli V 517. Studies on the effects of metabolites on growth of probiotic organisms as well as E. coli V 517 were also carried out to validate the hypotheses made in previous experiments. The results revealed that growth of tested probiotic bacteria increased with certain level of substrate concentration. In contrast, growth of E. coli V517 decreased with increasing concentration of lactic and acetic acids. It was postulated that mixed culture of S. faecalis T -110 and B. breve 048 as well as co-culture of S. faecalis T -110 and B. mesentericus TO-A exhibited commensal relationship, in which only one party benefits an the other is neither hanned nor benefited. Meanwhile, mixed culture of B. mesentericus TO-A and B. breve 048 showed a mutualistic association whereby both organisms profit from each other. Finally, in mixed culture of E. coli V517 and probiotic organisms, a strong antagonistic relationship was observed.